HUBUNGAN PENERIMAAN DIRI DENGAN MOTIVASI SEMBUH PASIEN COVID-19 KASUS KONFIRMASI TANPA GEJALA DI PATI - Heny Siswanti; Anny Rosiana Masithoh; Sri Karyati ((IJP) Indonesia Jurnal Perawat, 2022)
Background: The results preliminary studies through observation and interviews, where 7 out of 10 Covid-19 sufferers who undergo quarantine said that the motivation to recover is very lacking because they feel embarrassed and afraid if they come home after recovering later. This shows that the patient feels that he or she does not maintain socializing so that the patient is exposed to Covid-19. The patient also said that the urge to recover was reduced due to the staff who did not provide counseling and the lack of invitation from health workers to carry out healing therapies such as sunbathing and taking vitamins. People think that this disease is contagious and kills so that sufferers of Covid-19 do not dare to go home, are afraid and ashamed in people's lives because they must be isolated. As many as 3 sufferers of Covid-19 stated that they would live better lives by maintaining health and distance from other people. Covid-19 sufferers say they always get support from their families via cellphones by communicating every day. Objective: To determine the relationship between self-acceptance with motivation to heal covid-19 patients case without symptoms confirmation at Hotel Kencana Pati. Method: This type of research is the analytical method of correlation with the cross sectional approach. The number of samples used was 49 respondents who were selected by consecutive sampling. To analyze the data using the Spearman rank test. Results: The results of the Spearman rank analysis test obtained a value of r count 0.765 (strong) and a value of ρ value of 0.000 less than 0.05, it can be concluded that there is a strong relationship between self-acceptance with motivation to heal covid-19 patients case without symptoms confirmation at Hotel Kencana Pati.